Jonathan Franzen’s Novelistic Conversion - Merrill, Trevor Cribben (Mimesis, desire, and the novel, 2015)
Jonathan Franzen’s first two books, The Twenty-Seventh City (1988) and Strong Motion (1992), are a lot better than most contemporary works of fiction, but they are a lot worse than his third novel, The Corrections (2001), a family drama that vaulted Franzen to fame and established him as arguably the best American novelist of his generation. The modest critical success enjoyed by the first two novels, which were published within four years of each other, their similarly sprawling, postmodern plots, and their oft en cumbersome attempts to weave broader social issues into the narrative fabric, lead me to regard them